Perbandingan Ketahanan Ekonomi: Studi Kasus Indonesia dan Thailand dalam Sektor Pertanian - Kadek Deffa Arya Naufal; Aglisya Febriandhany; Ayasha Jihan Fatima; Dafa Pratama Sopiandi; Fatur Septian Rosadi (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
This study compares the economic resilience of Indonesia and Thailand in agricultural commodities such as rice, sugar, mangosteen, and mango. Both countries are agricultural countries in Southeast Asia and each makes a major contribution to the production and export of these commodities. Secondary data from government reports, international organizations, and previous research were used in a qualitative descriptive study. The results of the analysis show that Thailand excels in rice and mango production due to the use of advanced agricultural technology and efficient export strategies. However, Indonesia has great potential in the sugar and mangosteen industries, but faces challenges in production efficiency and competition in the international market. Through diversification policies and technological innovation, Thailand can adapt to the challenges of climate change and market price fluctuations. In contrast, Indonesia needs to improve agricultural infrastructure, increase supply chain efficiency, and create policies that help smallholder farmers. To improve economic resilience in these sectors, the study suggests increased regional cooperation and investment in technology.